OP0108 Bimekizumab, A Monoclonal Antibody That Inhibits both IL-17A and IL-17F, Produces A Profound Response in both Skin and Joints: Results of An Early-Phase, Proof-of-Concept Study in Psoriatic Arthritis. (15th July 2016) - Glatt, S.; Strimenopoulou, F.; Vajjah, P.; Shaw, S.; Ionescu, L.; Popa, S.; Baeten, D.
Abstract : Background: Bimekizumab (UCB4940) is a potent and selective monoclonal antibody inhibiting the activity of both IL-17A and IL-17F, which are key pro-inflammatory cytokines overexpressed in skin lesions of patients with psoriasis. 1 Blocking both IL-17A and IL-17F may provide a therapeutic advantage. Objectives: To study the safety/tolerability and efficacy of multiple-dose bimekizumab in patients with PsA with inadequate responses to at least 1 DMARD and/or 1 biologic DMARD (NCT02141763 ). Methods: 52 patients were randomized to receive either bimekizumab (N=38) or PBO (N=14). Four active dose-level groups were studied using a single loading dose (80–560 mg bimekizumab) administered at wk 0; further doses (40–320 mg bimekizumab) were administered at wks 3 and 6. ACR and PASI scores were examined; safety and PK variables were also investigated. Results: At baseline, patients had a mean SJC (66) of 12.6 and TJC (68) of 29.6, and mean baseline CRP of 12.5 mg/mL. For patients with skin involvement of >3% (N=23) a mean baseline PASI of 15.9 (SD=14.6) was observed. Onset of response was rapid for both skin and joints: by wk 8, an ACR20 RR of 80% was observed for the top 3 doses (N=32) compared with 17% in the PBO group (N=12). Clinically relevant responses in disease activity measures were observed to wk 20. A summary of results in skin and joints is presented in the table. Bayesian analysis on wk 8 data indicated a >99% probability that ACR score improvement, and ACR20 RR, were greater than PBO and exceed the pre-defined clinically relevant threshold (ACRntr : 0.31 and ACR20: 25%). Additionally, there was a high posterior probability of >99% that the bimekizumab ACR20 RR was greater than that reported for the current SOC biologic treatment, including anti-IL-17 therapies (59.7%) at wk 8. 2, 3 All doses of bimekizumab were well tolerated, with no unexpected safety findings. No patient discontinued due to treatment-emergent AEs. No treatment-related serious AEs were reported. Bimekizumab had a linear PK, with an expected half-life of ∼24 days. Conclusions: In patients with PsA, bimekizumab demonstrated rapid onset, sustained and deep efficacy on disease activity in skin and joints, and within this limited patient and exposure set, was safe and well tolerated. Bayesian analysis indicated that bimekizumab ACR20 RR is greater than that reported for current therapies including anti-IL-17A. Results support that inhibition of both IL-17A and IL-17F could provide additional clinical benefit in IL-17-mediated diseases. References: Johansen et al. Br J Dermatol 2009;160:319–24; McInnes et al. Lancet 2015;386:1137–46; McInnes et al. Lancet 2013;382:780–9 Acknowledgement: This study was UCB Pharma funded. Disclosure of Interest: S. Glatt Shareholder of: UCB, Employee of: UCB, F. Strimenopoulou Employee of: UCB, P. Vajjah Shareholder of: UCB, Employee of: UCB, S. Shaw Shareholder of: UCB, Employee of: UCB, L. Ionescu Employee of: UCB, S. Popa: None declared, D. Baeten Grant/research support from: AbbVie, Pfizer, MSD, UCB, Novartis, Boehringer Ingelheim, Consultant for: AbbVie, Pfizer, MSD, UCB, Novartis, Boehringer Ingelheim, Roche, Eli Lilly, BMS